Children's behavioural and emotional reactions towards living with congenital heart disease in Saudi Arabia: A grounded theory study - Nada Dahlawi; Linda Milnes; Veronica Swallow (Wiley, 2024)
Abstract Background A high incidence of children with congenital heart disease (CHD) was found in Saudi Arabia (SA). International literature reports that children with CHD exhibit behavioural and emotional issues due to experiencing hospitalisation and clinical treatments combined with a dearth of qualitative understanding of the experiences of younger children with CHD. Therefore, the aim was to explore the behaviour and emotions of 4-10‐year‐olds with CHD in SA through children's accounts of their own experiences and parental proxy reports of children's behaviour and emotions. Methods Charmaz's constructivist grounded theory (GT) approach was used. Twenty single semi‐structured interviews of 10 child/parent dyads were undertaken at a hospital clinic in SA. Children's interviews were combined with an arts‐based approach using drawings, pictures and faces of emotions (emojis). Constant comparison analysis was undertaken. Consolidated Criteria for Reporting Qualitative Research guidelines was followed in reporting this study. Findings A substantive GT: children's behavioural and emotional reactions towards stressors related to living with CHD was developed and provides new insights into children's and parents' perceptions of the children's behavioural and emotional reactions to living with CHD in SA. The theory proposes that children's reactions to living with CHD relate to medical treatment stressors, sociocultural stressors and physical change stressors. Several further factors influenced children's responses to these stressors. Conclusion Children and parents in SA contributed to a new understanding of the relationship between CHD and children's behavioural and emotional reactions. In addition, findings support the need for early assessment of behaviour and emotions among children with CHD and the application of preventative and supportive measures for the children and their families in SA. Patient or Public Contribution Before the research commenced, the developmental appropriateness of the proposed arts‐based data collection tools was tested with three healthy children aged 6-9 years old; the tools were then revised accordingly before the interviews were undertaken.